2014
DOI: 10.1074/jbc.m113.532929
|View full text |Cite|
|
Sign up to set email alerts
|

A Positive Cooperativity Binding Model between Ly49 Natural Killer Cell Receptors and the Viral Immunoevasin m157

Abstract: Background: m157 is a cytomegalovirus immunoevasin that binds Ly49 natural killer cell receptors. Results: Kinetic and thermodynamic analyses revealed the mechanism underlying the Ly49/m157 interaction. Conclusion:The binding mechanism is characterized by positive cooperativity and conformational selection. Significance: This mechanism provides a biophysical framework for interpreting crystal structures of Ly49 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In agreement with the model, biochemical analyses confirmed that trans binding of MHC-I by Ly49 dimers occurs in a bivalent fashion, whereas cis binding is monovalent ( 106 ). Moreover, Ly49 receptors appear able to switch between backfolded and extended conformations ( 108 , 123 ).…”
Section: Trans and Cis Interactions Of Lymentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the model, biochemical analyses confirmed that trans binding of MHC-I by Ly49 dimers occurs in a bivalent fashion, whereas cis binding is monovalent ( 106 ). Moreover, Ly49 receptors appear able to switch between backfolded and extended conformations ( 108 , 123 ).…”
Section: Trans and Cis Interactions Of Lymentioning
confidence: 99%
“…In the backfolded conformation, by contrast, the Ly49 α3s stalk segment would not be accessible to m157, due to its intimate association with the NKD (Figure 8 A). For both the Ly49H–m157 and Ly49I–m157 interactions, kinetic and thermodynamic measurements showed that binding involves a conformational selection mechanism where only the extended conformation of Ly49 is able to bind a first m157 ligand, followed by binding of a second m157 ( 123 ). The interaction is characterized by strong positive cooperativity, such that the second m157 binds the Ly49 homodimer 1,000-fold more tightly than the first.…”
Section: Ly49 Recognition Of a Viral Immunoevasinmentioning
confidence: 99%